NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAAnalysis of the correlation between troponin I level evaluated in the early period after heart transplantation and the histopathological findings of the transplanted heart - Wierzbicki, Karol; Sobczyk, Dorota; Milaniak, Irena; Bochenek, Maciej; Ciołczyk-Wierzbicka, Dorota; Frasik, Wiesław; Rudnicka-Sosin, Lucyna; Kapelak, Bogusław; Drwiła, Rafał; Bartuś, Krzysztof; Przybyłowski, Piotr; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : Troponin is a well-known marker of myocardial injury of various etiology. There are not enough data about the correlation between ischemic injury diagnosed in a biopsy specimen of the transplanted heart and troponin levels measured in the following days after heart transplantation (HTX). Aim of the study was to evaluate the correlation of post-reperfusion myocardial ischemia in the early post-transplant period with the serial troponin I measurements. Material and methods : We retrospectively analyzed a group of 37 patients (5 female, 32 male), average age 45.6 ±14.3 years, after orthotopic heart transplantation (HTX), with an en- domyocardial biopsy performed on day 10 (±1) after HTX. Patients with histopathologically confirmed acute rejection were excluded from the analysis. The study population was divided into two subgroups regarding the ischemic changes in histopathology specimens of the transplanted heart. Results : Post-reperfusion ischemic changes confirmed by endomyocardial biopsy were present in 20 patients. Statistical analysis did not reveal any statistically significant differences in the mean troponin levels in consecutive days after HTX, regarding the presence of ischemia. A major difference in mean troponin levels between the study groups was observed at days 0 and 3, and a minor one at day 1 after HTX. Conclusion : In the study group no statistical relationship was found between troponin I levels measured in the first days after HTX and the presence of ischemic changes noted in routine endomyocardial biopsy material (10th day after HTX).